The true believer : - Hoffer, Eric (Harper & Brothers, 1951)
The True Believer is a landmark in the field of social psychology, and even more relevant today than ever before in history. Called a “brilliant and original inquiry” and “a genuine contribution to our social thought” by Arthur Schlesinger, Jr., The True Believer is mandatory reading for anyone interested in the machinations by which an individual becomes a fanatic.